Α-PD-1 therapy elevates Treg/Th balance and increases tumor cell pSmad3 that are both targeted by α-TGFβ antibody to promote durable rejection and immunity in squamous cell carcinomas. Issue 1 (4th March 2019) - Dodagatta-Marri, E.; Meyer, D. S.; Reeves, M. Q.; Paniagua, R.; To, M. D.; Binnewies, M.; Broz, M. L.; Mori, H.; Wu, D.; Adoumie, M.; Del Rosario, R.; Li, O.; et al.
Abstract : Background: Checkpoint blockade immunotherapy has improved metastatic cancer patient survival, but response rates remain low. There is an unmet need to identify mechanisms and tools to circumvent resistance. In human patients, responses to checkpoint blockade therapy correlate with tumor mutation load, and intrinsic resistance associates with pre-treatment signatures of epithelial mesenchymal transition (EMT), immunosuppression, macrophage chemotaxis and TGFβ signaling. Methods: To facilitate studies on mechanisms of squamous cell carcinoma (SCC) evasion of checkpoint blockade immunotherapy, we sought to develop a novel panel of murine syngeneic SCC lines reflecting the heterogeneity of human cancer and its responses to immunotherapy. We characterized six Kras-driven cutaneous SCC lines with a range of mutation loads. Following implantation into syngeneic FVB mice, we examined multiple tumor responses to α-PD-1, α-TGFβ or combinatorial therapy, including tumor growth rate and regression, tumor immune cell composition, acquired tumor immunity, and the role of cytotoxic T cells and Tregs in immunotherapy responses. Results: We show that α-PD-1 therapy is ineffective in establishing complete regression (CR) of tumors in all six SCC lines, but causes partial tumor growth inhibition of two lines with the highest mutations loads, CCK168 and CCK169. α-TGFβ monotherapy results in 20% CR and 10% CR of established CCK168 and CCK169 tumors respectively, together with acquisition of long-term anti-tumor immunity. α-PD-1 synergizes with α-TGFβ, increasing CR rates to 60% (CCK168) and 20% (CCK169). α-PD-1 therapy enhances CD4 + Treg/CD4 + Th ratios and increases tumor cell pSmad3 expression in CCK168 SCCs, whereas α-TGFβ antibody administration attenuates these effects. We show that α-TGFβ acts in part through suppressing immunosuppressive Tregs induced by α-PD-1, that limit the anti-tumor activity of α-PD-1 monotherapy. Additionally, in vitro and in vivo, α-TGFβ acts directly on the tumor cell to attenuate EMT, to activate a program of gene expression that stimulates immuno-surveillance, including up regulation of genes encoding the tumor cell antigen presentation machinery. Conclusions: We show that α-PD-1 not only initiates a tumor rejection program, but can induce a competing TGFβ-driven immuno-suppressive program. We identify new opportunities for α-PD-1/α-TGFβ combinatorial treatment of SCCs especially those with a high mutation load, high CD4+ T cell content and pSmad3 signaling. Our data form the basis for clinical trial of α-TGFβ/α-PD-1 combination therapy (NCT02947165 ).